2016
DOI: 10.1037/tra0000080
|View full text |Cite
|
Sign up to set email alerts
|

An epidemiologic study of childhood sexual abuse and adult sleep disturbances.

Abstract: Objective Childhood sexual abuse (CSA) is linked to negative consequences, including insomnia. Few studies have examined enduring effects of CSA on adult insomnia. Given the relationship between sleep and poor health, a better understanding of these effects has clinical implications. Method We used a representative sample of adult twins. Both men and women were assessed with a broad variable representative of CSA, while a subset of females (n=424) were given additional items that captured escalating physical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
3

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(22 citation statements)
references
References 49 publications
(91 reference statements)
0
17
3
Order By: Relevance
“…The existing studies of sleep and trauma in clinical samples (Aubert et al, 2016;Hamilton et al, 2018), including the current, have not found any association between sexual abuse and insomnia. This is in contrast to the studies of non-clinical samples (Kajeepeta et al, 2015;Lind, Aggen, Kendler, York, & Amstadter, 2016;Steine et al, 2012). Our data have no indications of why.…”
Section: Discussioncontrasting
confidence: 99%
“…The existing studies of sleep and trauma in clinical samples (Aubert et al, 2016;Hamilton et al, 2018), including the current, have not found any association between sexual abuse and insomnia. This is in contrast to the studies of non-clinical samples (Kajeepeta et al, 2015;Lind, Aggen, Kendler, York, & Amstadter, 2016;Steine et al, 2012). Our data have no indications of why.…”
Section: Discussioncontrasting
confidence: 99%
“…Participants for the current study were taken from the Virginia Adult Twin Studies of Psychiatric and Substance Use Disorders (VATSPSUD; total N ∼ 7500), a large longitudinal twin study of Caucasian adults, described in detail elsewhere (Kendler & Prescott, ). Similar to existing papers with this data set (e.g., Kendler et al., ; Lind et al., ; Lind, Aggen, Kendler, York, & Amstadter, ), this sample is being used as an epidemiological sample, with analyses controlling for twin status. We utilized data from female–female (FF) and male–male and male–female (MMMF) twins assessed at two separate interview waves (referred to here as Time 1 [study wave 1 for FF and MMMF] and Time 2 [study wave 3 for FF and wave 2 for MMMF]).…”
Section: Methodsmentioning
confidence: 99%
“…Direct and indirect human and animal stress research supports the important supraordinate role of CS on stress system and GCs, linking circadian misalignment in ELS/CT-related pathophysiology and potentially resulting in the extensive comorbidities of ELS/CT through an impaired homeostatic balance. Some animal (332), but-most importantly-numerous human studies including large cohorts, have repeatedly confirmed that ELS/CT is independently associated with enduring adult sleep disruption including global sleep pathology (i.e., insomnia), as well as specific types of sleep problems, such as shortened total sleep time, prolonged sleep onset latency, decreased sleep efficiency, increased number of awakenings, nightmare related distress, sleep apnea and higher nocturnal activity in a probably dose-response manner (333)(334)(335)(336)(337)(338)(339)(340)(341)(342)(343)(344).…”
Section: Sleep and Circadian Systemmentioning
confidence: 97%